Compressive Mechanical Properties of a Novel Recycled Aggregate Concrete with Recycled Lightweight Aggregate - Anjun Li; Gaoqiang Zhou; Xianggang Zhang; Ercong Meng (Advances in Materials Science and Engineering)
A novel recycled aggregate concrete was prepared by replacing the natural aggregate with recycled lightweight aggregate. Subsequently, the mechanical properties and compressive stress-strain constitutive relation of the recycled lightweight aggregate concrete (RLWAC) were explored. For this purpose, the recycled lightweight aggregate (RLWA) replacement ratio (0%, 25%, 50%, 75%, and 100%) was selected as a variable, and the compressive strength of 15 cube and 30 prism specimens was evaluated. The failure morphology of the specimen was subsequently characterized, along with the cubic compressive strength, axial compressive strength, peak strain, ultimate strain, and other performance indices. The influence of the replacement ratio for the specimen indices of the RLWAC was also analyzed. It was observed that the dry apparent density of RLWAC decreased gradually on increasing the replacement ratio. Compared with 0% replacement ratio, a decrease of 6.50%, 11.39%, 21.84%, and 27.54% was observed, respectively. On enhancing the RLWA replacement ratio, the compressive strength, peak strain, and ultimate strain of RLWAC were observed to be gradually reduced. As the replacement ratio was increased from 75% to 100%, the peak strain was noted to decrease the most by about 6.8%. As the replacement ratio was increased from 50% to 75%, the ultimate strain decreased the most by about 14.2%. Based on the experimental findings, the functional relationships of the strength indices and the conversion value of each strength index with the replacement ratio were also established. Finally, based on the model proposed by the existing model, the stress-strain equation of RLWAC was developed, and the fitting results were observed to be in good agreement with the test results.